2018
DOI: 10.1039/c8ra04405h
|View full text |Cite
|
Sign up to set email alerts
|

Interconnecting semiconducting molecules with non-conjugated soft linkers: a way to improve film formation quality without sacrifice in charge mobility

Abstract: For small molecular semiconductors, interconnecting their molecules with non-conjugated soft linkers has been demonstrated to be a good way for improving their film formation quality while keeping their mobility intact for OFETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Despite aggregation in solution often leading to reduced thinfilm uniformity relative to polymeric materials, 166 small molecules have nonetheless provided a major contribution to the fabrication of organic semiconducting devices. The most comprehensive review to date identified 643 reported small molecules used in field-effect transistors, compared to only 66 distinct polymers for the same purpose.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Despite aggregation in solution often leading to reduced thinfilm uniformity relative to polymeric materials, 166 small molecules have nonetheless provided a major contribution to the fabrication of organic semiconducting devices. The most comprehensive review to date identified 643 reported small molecules used in field-effect transistors, compared to only 66 distinct polymers for the same purpose.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Another strategy to reduce the stiffness of the backbone of semiconducting polymers is to add conjugation-break spacers . This strategy also leads to tradeoffs between the electrical properties and the softness, with the modulus of these polymers falling within the 100–1000 MPa range. …”
Section: Introductionmentioning
confidence: 99%